Prevalence of dental anxiety level in 6- to 12-year-old South Indian children - Vinod Kumar; E V Soma Sekhar Goud; Neeraja Turagam; Durga Prasad Mudrakola; Kranti Kiran Reddy Ealla; Praveen Haricharan Bhoopathi (Wolters Kluwer Medknow Publications, 2019)
Background: Dental anxiety is one of the prime reasons for discouraging children to receive dental treatment. Measurement of the dental anxiety is very useful to know the prevalence level among 6- to 12-year-old children. Thus, the aim of the study was to determine the dental anxiety among 6- to 12-year-old children using Modified Dental Anxiety Scale (MDAS) score. Materials and Methods: A total of 400 south Indian children in the age group of 6-12 years who had visited Dental College and Hospital were recruited in the study. Dental anxiety was measured before dental treatment using MDAS. Statistical analysis was performed using Wilcoxon signed rank test. Results: Of the 400 children, 240 (61.5%) had severe dental anxiety, 92 (23%) had mild anxiety, and 78 (17%) had no anxiety. Females had higher anxiety level compared to males. Many study subjects answered that local anesthesia (LA) injection was considered most fearful. Dental anxiety was highest in smaller age groups. Conclusion: In our research, high percentage of children had dental anxiety, so counseling before dental visits is very important to reduce the dental anxiety among these 6- to 12-year-old children.